2011
DOI: 10.1038/ng.981
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies FCGR2A as a susceptibility locus for Kawasaki disease

Abstract: Kawasaki disease is a systemic vasculitis of unknown etiology, with clinical observations suggesting a substantial genetic contribution to disease susceptibility. We conducted a genome-wide association study and replication analysis in 2,173 individuals with Kawasaki disease and 9,383 controls from five independent sample collections. Two loci exceeded the formal threshold for genome-wide significance. The first locus is a functional polymorphism in the IgG receptor gene FCGR2A (encoding an H131R substitution)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
220
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(237 citation statements)
references
References 45 publications
3
220
2
4
Order By: Relevance
“…This is an exciting time in KD research because a practicable biomarker (eg., IP-10) with extremely high sensitivity and specificity has been identified (26), and the genetic contributions to KD are becoming clearer than ever (23, 39,52,53). Follow-up research based on these achievements could clarify the pathogenic mechanisms that lead to KD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an exciting time in KD research because a practicable biomarker (eg., IP-10) with extremely high sensitivity and specificity has been identified (26), and the genetic contributions to KD are becoming clearer than ever (23, 39,52,53). Follow-up research based on these achievements could clarify the pathogenic mechanisms that lead to KD.…”
Section: Resultsmentioning
confidence: 99%
“…To identify novel genetic factors that predispose an individual to KD, GWASs for KD in a Han Chinese (51,52) and Japanese population (53) were recently conducted, and novel critical susceptibility loci located in the CD40, B-lymphocyte kinase (BLK), FCGR2A, as well as ITPKC gene regions were identified. These findings highlighted the importance of B-cell or T-cell activation by candidate genes to the pathogenesis of this inflammatory disease (Figure 1).…”
Section: Genetics and Kawasaki Diseasementioning
confidence: 99%
“…As shown in Figure 1, a final total of 2122 patients with KD and 1565 controls were included in the metaanalysis (Taniuchi et al, 2005;Biezeveld et al, 2007;Khor et al, 2011;Ji et al, 2013;Yan et al, 2013;Chatzikyriakidou et al, 2014). The characteristics of these eight case-control studies from six articles are presented in Table 1; these contain studies of two Caucasian (Biezeveld et al, 2007;Chatzikyriakidou et al, 2014) and six Asian (Taniuchi et al, 2005;Khor et al, 2011;Ji et al, 2013;Yan et al, 2013) populations. The distribution of genotypes in the controls was consistent with HWE in all studies except for Taniuchi et al (2005).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Until now, genome-wide association studies and linkage analyses have reported a few genetic loci that have shown association with KD in subjects of Japanese, European, Korean, and Taiwanese descent (Burgner et al, 2009), including the IgG receptor gene FCGR2A. A point mutation (A→G) in FCGR2A (reference/alternative) resulting in an amino acid change at position 131, histidine (His131) to arginine (Arg131), is located in the second extracellular immunoglobulin-like domain of the FCGR2A protein (H131R); it has been suggested that this variation this variation might be related to the development of KD (Khor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…IVIG appears to have a generalized anti-inflammatory effect. Possible mechanisms of action include modulation of cytokine production, neutralization of bacterial super-antigens or other etiologic agents, augmentation of regulatory T cell activity (TGF-), (23,26) suppression of antibody synthesis and inflammatory markers (CD40-CD40L, nitric oxide, and iNOS expression),(60-62) provision of anti-idiotypic antibodies, Fc-gamma receptor, (63) and balancing Th1/Th2 responses. (28)(29)(30) KD patients should be treated with a single 12-hour infusion of 2 g/kg IVIG together with aspirin in the acute phase with fever or inflammation progression without fever.…”
Section: Intravenous Immunoglobulin (Ivig or Ivgg) Responsivenessmentioning
confidence: 99%